Redescriptions of two closely related East Asian flatfish species of the genus Pleuronichthys - Yokogawa, Kōji; Watanabe, Ken-Ichi; Ogihara, Gota (Zootaxa, 2016)
Because of the taxonomic confusion, including misapplication of their scientific names, resulting from the morphological similarity of two East Asian flatfish species, Pleuronichthys lighti Wu, 1929 and Pleuronichthys cornutus (Temminck & Schlegel, 1846), both species are redescribed, with particular emphasis on some new key characters. New common names are proposed for each species.